2020
DOI: 10.2147/dddt.s287442
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin- and Cyclopamine-Loaded Liposomes to Enhance Therapeutic Efficacy Against Hepatic Fibrosis

Abstract: Background and Purpose Hepatic fibrosis is a public health problem characterized by activation of hepatic stellate cells (HSCs), which triggers excessive production of extracellular matrix (ECM). Inhibition of HSC activation may be an effective treatment. Since various pathways control HSC activation, a combination of drugs with different mechanisms may be more effective than monotherapy. Methods Here, we prepared liposomes loaded with curcumin and cyclopamine to inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Our results align well with previous reports that highlighted the attenuation of liver fibrosis through abrogation of the Hedgehog pathway ( Jiayuan et al, 2020 ; Zhang et al, 2020 ). Moreover, Michelotti et al (2013) reported that SMO deletion from α-SMA + myofibroblasts caused inhibition of liver fibrosis.…”
Section: Discussionsupporting
confidence: 93%
“…Our results align well with previous reports that highlighted the attenuation of liver fibrosis through abrogation of the Hedgehog pathway ( Jiayuan et al, 2020 ; Zhang et al, 2020 ). Moreover, Michelotti et al (2013) reported that SMO deletion from α-SMA + myofibroblasts caused inhibition of liver fibrosis.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, inhibiting Hh signaling will be an effective therapeutic target. It has been previously reported liver fibrosis was attenuated by Hh inhibitors, such as cyclopamine ( Zhang et al, 2020 ), vismodegib ( Pratap et al, 2012 ), and GANT61 ( Jiayuan et al, 2020 ). The present study showed that GPs suppressed the activation of Hh signaling both in CCl 4 /2-AAF-treated rats and Mdr2 −/− mice.…”
Section: Discussionmentioning
confidence: 99%